Penguasaan Konsep dan Sikap Ilmiah Siswa kelas V Melalui Pembelajaran RADEC pada Materi Pengolahan Air dengan Berbantuan Media Aplikasi Zoom - Agista, Dea Inggit; Sujana, Atep; Saputra, Yudha Munajat (Jurnal Pena Ilmiah, 2021)
This study aims to see ability master concepts and scientific attitudes of students that arise through the application of the Read-Answer-Discuss-Explain-Create (RADEC) learning model. This study uses descriptive qualitative research methods. The participants in this study consisted of 15 fifth grade students in an elementary school in South Sumedang District, Sumedang Regency. The data was collected through observations on the implementation of learning which included teacher performance, observations on student activities, observations of scientific attitudes and tests of students' conceptual mastery abilities. Observations are carried out during learning process, while student ability tests are given at the beginning and end learning, then analyzed through data reduction, presentation and conclusions. From this research, the results obtained are that the implementation of learsning given the treatment of the RADEC learning model carried out online effectively through the Zoom application, Mastery of students' concepts is well achieved as evidenced, and all these scientific attitudes emerge and can foster good self-efficacy which has positive values after being given the RADEC learning.